(untitled) (Journal of Misan Researches, 2024)
The aim of the research is to identify the degree of inclusion of international test skills (PISA) science and the skills of the twenty-first century in the biology book for the sixth scientific grade in the Republic of Iraq. The research sample was represented in the biology book for the sixth scientific grade in the academic year 2022/2023. In order to collect data and achieve the research goals, the researcher used the descriptive-analytical method based on the analysis card developed and included the international test skills (PISA) the main sciences and their sub-indicators, as well as the ten skills of the twenty-first century and its sub-indicators. The veracity and consistency of its data have been verified The results of the research showed that the main skills of testing (PISA) sciences were included in the content of the biology book for the sixth scientific grade in different proportions, as the skill of scientific competencies came in first place and reached (60%), and the skill of knowledge of (PISA) science ranked second by (33%), and the skill of contexts (PISA) science and its applications ranked last (7%), while the degree of including the skills of the twenty-first century came at a low, reaching (30%) except for critical thinking and problem-solving skills. The researcher recommended several recommendations, most notably building the curriculum in all stages of education in light of the skills of the twenty-first century, the need to include the skills of testing (PISA) in He wrote science for the middle stage, and worked to change the stereotyping of school tests so that they harmonize with international tests